Analisis Kinerja Buck Boost Converter LTC3780 Pada Sistem Micro Combustion Untuk Pengisian Baterai Lithium - Arrafi Nur Hidayatullah; Herman Saputro (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
The use of electronic devices or equipment is inseparable from daily life, which contributes to the increasing demand for electrical energy. The growing electricity consumption in Indonesia encourages many people with various creative ideas to develop tools or generate electricity independently by utilizing existing energy sources. One solution for supplying electrical energy is micro-scale power generation (micropower generation). In this context, the converter module used is a Thermo Electric Generator (TEG). TEG can generate electrical voltage proportional to the temperature difference between the hot and cold sides. The heat source is obtained from the combustor, while the cooling temperature is provided by a cooling system. One of the solutions to stabilize the electrical energy produced by the TEG is to use a buck-boost converter. This research aims to analyze the performance of the LTC3780 buck-boost converter concerning the electrical energy produced by the micropower generation system for battery charging and to determine the efficiency of the LTC3780 buck-boost converter for lithium battery charging with various cell configurations. This research employs a quantitative descriptive data analysis technique combined with a comparative approach. The results of this study indicate that the use of the LTC3780 affects the voltage stability during battery charging, and the number of battery cells also influences the output voltage of the LTC3780. The 3-cell configuration provides the highest and most consistent output voltage throughout the testing period. Furthermore, battery charging efficiency tends to be more optimal with fewer battery cells, particularly in the 1-cell and 2-cell configurations. Conversely, the greater the number of cells used, the lower the charging efficiency tends to be.